Efektivitas Penggunaan Kecerdasan Buatan (AI) dalam Menunjang Kurikulum Berbasis Cinta pada Pembelajaran PAI di MTs Satu Atap Mi’rajussibyan NWDI Selanglet - Fatmawati (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
This study aims to examine the effectiveness of Artificial Intelligence (AI) in supporting the implementation of the Love-Based Curriculum in Islamic Religious Education (PAI) learning at MTs Satu Atap Mi’rajussibyan NWDI Selanglet, Central Lombok, West Nusa Tenggara. A mixed method approach with a sequential explanatory design was employed, combining quantitative and qualitative approaches. Quantitative data was gathered through questionnaires distributed to 90 grade VIII students and 12 PAI teachers, while qualitative data was obtained through in-depth interviews, observation of 15 learning sessions, and documentation analysis. Results indicate that AI use significantly increased student learning motivation by 79.6%, strengthened teacher-student affective bonds, and reinforced the values of compassion and empathy as the core of the Love-Based Curriculum. Regression analysis yielded R² = 0.641, and paired t-test results showed t(89) = 14.72, p < 0.001. AI was found to contribute to three key dimensions: facilitating empathy, enabling personalized attention, and designing meaningful learning experiences. This study affirms that AI integration in PAI is not merely technological modernization, but a pedagogical endeavor to create more humane, loving, and meaningful education aligned with Islamic values.